Building Climate Coalitions on Preferential Free Trade Agreements - Thomas Kuhn; Radomir Pestow; Anja Zenker (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2017)
In this paper, we discuss the endogenous formation of climate coalitions in the tradition of the issue-linkage literature. In particular, we propose a preferential free trade agreement on which a climate coalition should be built. The basic idea is that the benefits of free trade provide strong incentives for free riders to join the coalition. As a framework, a multi-stage strategic trade model is used in which a country may discourage greenhouse gas emissions by setting an emissions cap effective on a permit market. In addition, a discriminatory import tariff is imposed on dirty goods. However, at the heart of our approach are the trade privileges granted to coalition members shifting the terms of trade favourably without prodiving incentives towards eco-dumping. As a main result, we find that trade liberalisation is much more effective in building climate coalitions than a single-issue environmental agreement. The parametrical simulation of the model in particular shows that participation in joint emission reduction is higher, consumption patterns are more environmentally friendly, and coalitional welfare is improved. As a policy implication, negotiations on climate treaties and free trade arrangements should be integrated.
Keywords: Q54; Q56; F18; F15; Q58; 330; Climate Change; International Environmental Agreements; Free Trade; Issue Linkage; Tradable Permits; Strategic Trade Policy